The Law of Usury from the perspective of Quraish Shihab in the Qur'an - Ruslan, Muhammad (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2024)
Historically, the Jews were a people who had tried to legitimize anything that had been forbidden by Allah SWT, one of which was legitimizing usury, so it is well-known that from the past until now, the act of usury is difficult to separate. The Qur'an itself has explained in detail the stages of prohibiting usury explicitly. The Qur'an prohibits usury with the limitation of adh'āfan mudhā'afan. The main research topic of this thesis is (1) How is the prohibition of usury in the Qur'an? (2) How is the analysis of usury according to Quraish Shihab's thoughts in the Tafsir Al-Misbah?, (3) What is the sociological background of the cause of the decline of usury (Asbabul Nuzul ayat riba)? This type of research is a literature review method (library research). The results of this study are, First: The prohibition of usury in the Qur'an, scholars agree that: (a) usury is something that is prohibited because of the verses that explain the prohibition of usury. (b) the prohibition of usury in the Qur'an has relevance to the movement of the real sector in the economy, Second, Usury according to Quraish Shihab, that people who practice usury, their efforts, actions and all their circumstances will experience turmoil, their souls will not be at peace. Third, the sociological background of the reason for the decline of usury begins from the history of usury starting from the settlement of the Tsaqif tribe which is located about 75 miles southeast of Mecca, they are familiar with usury practices